Unlocking Senegal’s dairy potential: The role of improved feed and stabling practices - Chan, Derek; Houessionon, Prosper; Whitbread, Anthony; Worou, Nadine; Wane, Abdrahmane (International Livestock Research Institute, 2025)
Dairy demand in Senegal exceeds domestic supply, despite the country’s large cattle herd and significant potential to expand production. To realize this potential, however, challenges related to low productivity, seasonal fluctuations, and limited market linkages must be addressed. This study analyzes the effects of introducing improved cowpea forage and sheltering practices on milk production and revenues among agropastoral producers in the Louga and Thiès regions, using quantitative simulations within a System Dynamics model. Results indicate that improved forage enhances milk output throughout the year, including during the dry season and sheltering can help improve it further. However, it is important to note that the improve forage grown must cover the needs for the entire dry season, else the cost of purchased feed may outweigh the benefits in increased productivity. Improved market access is also essential for translating milk productivity gains into higher revenues, particularly in areas where marketing opportunities remain limited.